The shifting powers of educational knowledge: power relations between sociology and economics of education. Issue 2 (4th March 2021) - Allais, Stephanie; Shalem, Yael
ABSTRACT: This paper considers the 'hope' and 'disappointments' experienced over time about the results of rapid educational expansion, as well as the research agenda which aims to improve educational outcomes in the developing world and particularly in Africa. Our interest is in the development and nature of policy-oriented bodies of knowledge that address the issue of educational inequality in poor countries. More specifically, we examine the state of knowledge production in sociology of education in relation to the question of educational inequality. We do this through an exploration of its interface with economics of education, starting with an examination of literature in the developed world. We argue that there was an initial collaboration in the 1950s, shifting to something of a separation from the 1980s, to what could be seen as a colonization of education in research on developing countries. This is facilitated by the way in which sociology of education has developed into silos of topic-based research—reducing its explanatory and political power. Some silos are marginalized, and some are dominated by claims on 'what works' produced by economists.